2022
DOI: 10.1021/acsbiomaterials.1c01399
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Dimensional Printable Hydrogel Formulation for the Local Delivery of Therapeutic Nanoparticles to Cervical Cancer

Abstract: Cervical cancer is the fourth most common malignancy among women. Compared to other types of cancer, therapeutic agents can be administrated locally at the mucosal vaginal membrane. Thermosensitive gels have been developed over the years for contraception or for the treatment of bacterial, fungal, and sexually transmitted infections. These formulations often carry therapeutic nanoparticles and are now being considered in the arsenal of tools for oncology. They can also be three-dimensionally (3D) printed for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 68 publications
2
16
0
Order By: Relevance
“…Another study found that the survival rate of Hela cells cultured with 30 mg-mL-1 SOLE/PEGDA decreased from 72.3% to 41.7% under NIR irradiation in poly(ethylene glycol) bisacrylate (PEGDA) composite hydrogels loaded with spinach extract (SOLE, a natural photosensitizer). It indicates that SOLE/PEGDA hydrogels are antitumor active in PDT treatment [57].…”
Section: Light-responsive Hydrogelsmentioning
confidence: 95%
“…Another study found that the survival rate of Hela cells cultured with 30 mg-mL-1 SOLE/PEGDA decreased from 72.3% to 41.7% under NIR irradiation in poly(ethylene glycol) bisacrylate (PEGDA) composite hydrogels loaded with spinach extract (SOLE, a natural photosensitizer). It indicates that SOLE/PEGDA hydrogels are antitumor active in PDT treatment [57].…”
Section: Light-responsive Hydrogelsmentioning
confidence: 95%
“…As with liposomes, hydrogels can also be thermoresponsive and be used for specific heat-triggered drug release. Such thermoresponsive gels undergo a sol-to-gel transition when heated to a specific temperature (i.e., low critical gelation temperature), leading to drug release [ 153 , 154 ]. Several studies investigated thermo- and non-thermoresponsive GNP–hydrogel hybrids for cancer therapy.…”
Section: Organic Gnp Nanohybrid Chemotherapeutic Platformsmentioning
confidence: 99%
“…Alginate-based thermosensitive hydrogels with GNPs were also studied for cancer therapy by Kiseleva et al, who used alginate combined with a thermosensitive polymer, PF127, to make thermoresponsive hydrogels for the encapsulation and release of GNPs. In this study, GNPs were used as the therapeutic agent to be released from the gel via gel dissolution and GNP diffusion without being triggered by heat [ 153 ]. Another alginate-based nanohybrid hosting both GNPs and iron oxide nanoparticles was studied for magnetically targeted drug delivery, PTT, and magnetic resonance imaging (MRI).…”
Section: Organic Gnp Nanohybrid Chemotherapeutic Platformsmentioning
confidence: 99%
“…Although multiple 3D printing methods exist, extrusion‐based printing has been most widely adopted due to its simplistic working principle and ease of use. [ 3,4 ] Inks used in extrusion 3D printing mainly consist of chemically modified versions of gelatin, [ 5–12 ] alginate, [ 13–16 ] hyaluronic acid, [ 17–20 ] collagen, [ 1,21,22 ] decellularized extracellular matrix, [ 23–25 ] or combinations of these. [ 26–35 ] The traditional approach for developing 3D printable inks has been to chemically modify naturally‐derived hydrogel materials to make them more printable, while attempting to maintain their favorable biological properties.…”
Section: Introductionmentioning
confidence: 99%
“…Although multiple 3D printing methods exist, extrusion-based printing has been most widely adopted due to its simplistic working principle and ease of use. [3,4] Inks used in extrusion 3D printing mainly consist of chemically modified versions of gelatin, [5][6][7][8][9][10][11][12] alginate, [13][14][15][16] hyaluronic acid, [17][18][19][20] collagen, [1,21,22] decellularized extracellular matrix, [23][24][25] or combinations of these. [26][27][28][29][30][31][32][33][34][35] The traditional approach for developing 3D printable inks invented a fabrication method that included extrusion printing followed by spraying a salt gelling agent at each layer.…”
Section: Introductionmentioning
confidence: 99%